Mechanisms of legal regulation of water security in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
Ensuring water security is a priority issue in many countries, demand and limited water resources, including groundwater resources in the world, require special attention.Changing ofclimate, management of the risks associated with extreme hydrological events, floods and droughts, also increases the urgency of ensuring water security.The article the concept of water security and legal mechanisms of water security in the Republic of Kazakhstanare considered.The methodological basis of the article is represented by the comparative legal method, formal logical, systematic structural analysis, scientific abstraction, the unity of objective and subjective in the development of legal processes, expert evaluation, analysis of documents and materials.The article reveals the main directions of water policy of the state, and proposes measures to form the system to ensure its implementation.Key words: water resources, water security, legal regulation, legal support.